As the Century Turns: Analytics, Empirics and Politics of Development - Thirukodikaval N. Srinivasan (Yale University, Economic Growth Center, 1997)
The paper celebrates John Fei's life and contributions to economics by viewing them in the context of recent theoretical and empirical literature on the economics and politics of growth. It summarizes the lessons from the literature and development experience since the end of the second world war on the roles of the state, markets and other institutions in the development process. It highlights a major lesson, on which there is substantial agreement if not a consensus, on the importance of openness to foreign trade, technologies and capital flows to growth and on the importance of participatory democracy for political sustainability of growth-promoting policies.
Keywords: F43; 330; Economic Development; Economic Growth; Openness and Growth; Foreign Trade and Growth; Technological Diffusion and Spillover; East Asian Economies; Political Economy; Authoritarianism and Development; Democracy and Development; Wachstumstheorie; Neue Wachstumstheorie; Exportinduziertes Wachstum; Innovationsdiffusion; Interventionismus; Demokratie; Ostasien; Theorie